2015
DOI: 10.1007/s00429-015-1119-3
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the ventral amygdalofugal pathway of the human limbic system using high spatial resolution diffusion tensor tractography

Abstract: The amygdala is known to have a role in core processes regulated by the limbic system such as motivation, memory, emotion, social behavior, self-awareness as well as certain primitive instincts. Several functional studies have investigated some of these brain tasks of the human limbic system. However, the underlying neuronal fiber connectivity of the amygdalo-diencephalon, as part of the limbic system, has not been delineated separately by prior diffusion-weighted imaging studies. The ability to trace the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…In previous reports based on histology, these fibers had been collectively called the amygdalofugal pathway. This tract was also recently revealed using in vivo DTI (Kamali et al, 2016). Several bundles could be differentiated as they entered the amygdala, forming clearly identifiable branches (Figures 2C–I, colored arrows).…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…In previous reports based on histology, these fibers had been collectively called the amygdalofugal pathway. This tract was also recently revealed using in vivo DTI (Kamali et al, 2016). Several bundles could be differentiated as they entered the amygdala, forming clearly identifiable branches (Figures 2C–I, colored arrows).…”
Section: Resultsmentioning
confidence: 53%
“…This area had been reproducibly recognized in previous in vivo DTI data, with a very strong structural alignment with the medial-lateral (red) orientation and intermediate FA values (0.4–0.6). In a recent study using in vivo DTI (Kamali et al, 2016) suggested that this area represented the amygdalofugal pathway. Our results confirm that claim, but it should be noted that the amygdalofugal pathway was only one of the constituents of this area, as annotated in the panels in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EAc encompasses a collection of subcortical regions with similar cellular compositions, neurochemistry, gene expression, and structural connectivity and it encompasses the bed nucleus of the stria terminalis (BST), the central nucleus of the amygdala (Ce), the sublenticular extended amygdala (SLEA), and portions of the accumbens shell (Alheid & Heimer, ; Fox, Oler, Tromp, Fudge, & Kalin, a; Oler et al, ; Yilmazer‐Hanke, ). It has long been recognized that the amygdala is connected to the BST via two major fiber bundles—the ventral amygdalofugal pathway (VA) and the stria terminalis (ST) (Avery et al, ; Kamali et al, ; Nauta, ) (Figure c)—and more recent tracing studies have identified a third, indirect pathway centered on the SLEA (Ce ↔ SLEA ↔ BSTL) (deCampo & Fudge, ; Fudge et al, ; Oler et al, ). Anatomically, the Ce and the BST are both poised to trigger or orchestrate key signs of fear and anxiety—including alterations in arousal, behavioral inhibition, and neuroendocrine activity—via dense mono‐ and polysynaptic projections to brainstem and subcortical effector regions (Fox et al, a; Freese & Amaral, ; Fudge et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: BL 5 basolateral nucleus of the amygdala; BM 5 basomedial nucleus of the amygdala; BST 5 bed nucleus of the stria terminalis; Ce 5 central nucleus of the amygdala; EAc 5 central division of the extended amygdala; La 5 lateral nucleus of the amygdala; Me 5 medial nucleus of the amygdala; SLEA 5 sublenticular extended amygdala [Color figure can be viewed at wileyonlinelibrary.com] the accumbens shell (Alheid & Heimer, 1988;Fox, Oler, Tromp, Fudge, & Kalin, 2015a;Oler et al, 2017;Yilmazer-Hanke, 2012). It has long been recognized that the amygdala is connected to the BST via two major fiber bundles-the ventral amygdalofugal pathway (VA) and the stria terminalis (ST) (Avery et al, 2014;Kamali et al, 2015Kamali et al, , 2016Nauta, 1961) (Figure 1c)-and more recent tracing studies have identified a third, indirect pathway centered on the SLEA (Ce $ SLEA $ BSTL) (deCampo & Fudge, 2013;Fudge et al, 2017;Oler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%